On the Potential of Function-Behavior-State (FBS) Methodology for the Integration of Modeling Tools - Alvarez Cabrera, A. A.; Erden, M. S.; Tomiyama, Tetsuo (Cranfield University Press, 2009)
Current mechatronic products tend to be very complex systems. A design team is necessary to develop such products, and appropriate modeling and design support tools are essential to aid the design team. The Automatic Generation of Control Software for Mechatronic Systems project aims to develop a set of prototype tools and a framework to integrate available modeling tools, aiming to support the generation of control software for mechatronic machines. The project contemplates functional modeling as part of this framework. This paper considers the Function-Behavior-State (FBS) model as a base for the functional model, and discusses its potential regarding integration of modeling tools.
Organised by: Cranfield University
Keywords: Function modeling; function behavior state; model integration; mechatronic systems design